258 Increase in Cycling Injuries During COVID-19: Unintended Consequences of Lockdown Restrictions in The United Kingdom. (4th May 2021) - Ansari, S A; Al-Jader, B; Khan, N; Younis, F
Abstract: Introduction: Higher number of cycling injuries were observed during the COVID-19 period in the United Kingdom at our institution. Many were serious injuries requiring hospitalisation and some requiring surgery. We investigated whether the lockdown led to a legitimate increase in incidence of cycling related injuries, resulting in a higher number of aerosol generating procedures (AGPs). This would assess whether the guidance on exercise during lockdown was appropriate, shaping future regulation in the case of cyclical lockdowns. Method: Records were screened retrospectively for cycling related injuries between April 1st and May 12th (lockdown) 2020 and for same period in 2019 as a control group. Injury severity, distribution and number of surgical procedures resulting from these were assessed. Results: The proportion of injuries due to cycling rose threefold (n = 55) during the COVID-19 lockdown. Injuries included fractures, soft tissue injuries and mixed injuries. An increase in the number of operative procedures (n = 13) and AGPs was also noted. Conclusions: Vague guidance and allowance of one form of outdoor exercise per day may have unintentionally contributed to rise in cycling injuries as many took to cycling for recreation. To make the guidance appropriate, usual forms of exercise should be encouraged, risk taking behaviours discouraged and safe cycling practices endorsed.